National infrastructure assessment : analysis of options for infrastructure provision in Great Britain. Interim results - Tran, M; Hall, J; Hickford, A; Nicholls, R; Alderson, D; Barr, S; Baruah, P; Beavan, R; Birkin, M; Blainey, S; Byers, E; Chaudry, M; et al. (Environmental Change Institute, University of Oxford, 2014)
Britain’s infrastructure has come into existence over many decades. We owe a considerable debt to the legacy left by the Victorian builders of railways, reservoirs and sewers. These ageing systems face considerable challenges in the future to serve a globalised economy. Moreover, Britain is committed to an 80% reduction in greenhouse gas emissions by 2050, which implies a transformation of energy supply, with knock-on effects that ripple through all infrastructure sectors. In the face of these challenges, there have been many calls for a longer term and more strategic approach to infrastructure provision in Great Britain. Decisions about infrastructure are long term commitments: wrong choices now could lead to future failures, and/or lock-in for future generations to inappropriate infrastructure systems, with high debts and maintenance costs and could also have important implications for sustainability. Thus we need a long term approach to analysing the options for national infrastructure provision across a wide range of plausible futures. That, however, is a complex technical task – much easier said than done. It involves understanding the drivers of demand for infrastructure services in the future and the ways in which the different infrastructure networks might cope with, and respond to that demand. The aim of the Infrastructure Transitions Research Consortium (ITRC) programme is to deliver that modelling capability for the UK. The ITRC has now developed an integrated system-of-systems model (NISMOD) that can simulate the long term performance of infrastructure networks in Great Britain. This analysis capability has been used to compare alternative long term strategies for infrastructure provision. In total we have examined 17 different options for infrastructure provision, to be implemented over the coming decades, under a wide range of scenarios of future demographic change, economic growth and climate change. This report presents interim results from that new analysis, helping to evaluate and compare alternative strategies for national infrastructure provision. Importantly, for the first time this report demonstrates how long term, cross-sectoral plans for infrastructure provision at a national scale can be mapped out and analysed.